Curriculum-Skill Gap in the AI Era: Assessing Alignment in Communication-Related Programs - Yaprak, Burak; Ercan, Sertac; Cosan, Bilal; Ecevit, Mehmet Zahid (Mdpi, 2025)
Artificial intelligence is rapidly reshaping skill expectations across media, marketing, and journalism, however, university curricula are not evolving at a comparable speed. To quantify the resulting curriculum-skill gap in communication-related programs, two synchronous corpora were assembled for the period July 2024-June 2025: 66 course descriptions from six leading UK universities and 107 graduate-to-mid-level job advertisements in communications, digital media, advertising, and public relations. Alignment around AI, datafication, and platform governance was assessed through a three-stage natural-language-processing workflow: a dual-tier AI-keyword index, comparative TF-IDF salience, and latent Dirichlet allocation topic modeling with bootstrap uncertainty. Curricula devoted 6.0% of their vocabulary to AI plus data/platform terms, whereas job ads allocated only 2.3% (chi(2) = 314.4, p < 0.001), indicating a conceptual-critical emphasis on ethics, power, and societal impact in the academy versus an operational focus on SEO, multichannel analytics, and campaign performance in recruitment discourse. Topic modeling corroborated this divergence: universities foregrounded themes labelled Politics, Power & Governance, while advertisers concentrated on Campaign Execution & Performance. Environmental and social externalities of AI-central to the Special Issue theme-were foregrounded in curricula but remained virtually absent from job advertisements. The findings are interpreted as an extension of technology-biased-skill-change theory to communication disciplines, and it is suggested that studio-based micro-credentials in automation workflows, dashboard visualization, and sustainable AI practice be embedded without relinquishing critical reflexivity, thereby narrowing the curriculum-skill gap and fostering environmentally, socially, and economically responsible media innovation. With respect to the novelty of this research, it constitutes the first large-scale, data-driven corpus analysis that empirically assessed the AI-related curriculum-skill gap in communication disciplines, thereby extending technology-biased-skill-change theory into this field.
Keywords: technological innovation; artificial intelligence; communication education; curriculum-skill gap; datafication; platform governance; labor-market analytics; natural language processing; topic modeling